ONLINE LEARNING: EFFECTIVENESS AND PERSPECTIVE OF LECTURERS IN PROFESSIONAL ETHICS COURSES - Puspito Rini, Puput; Anriani, Nurul; Munawar, Badri (Cakrawala Pedagogik, 2024)
The Covid-19 pandemic has triggered a drastic transformation in the world of education, especially at the higher education level. Significant increases in the use of online learning media occur in response to the need for adaptation to changing situations. Although the critical times of the pandemic have passed, the practice of online learning continues to grow rapidly. Online learning in the Professional Ethics course has become one of the alternatives in some colleges, but the effectiveness of such learning methods still needs to be studied more deeply from the point of view of the lecturers. An instrument to measure the effectiveness of online learning is developed and tested for its validity and reliability. The instrument has four dimensions: level of effort, student contribution, faculty skills, and learning outcomes. The study uses research and development methods involving 30 respondents, lecturers at Bestari University. The validity analysis results show that the entire online learning effectiveness instrument item is valid and acceptable. Nevertheless, the reliability of the Student Contributions dimension showed less satisfactory results. Furthermore, in this study, validity and reliability tests were carried out on the ethics instruments of the profession. The results of the research concluded that the research instruments are valid and reliable in measuring the ethical variables of the occupation. With adequate validity and reliability, this research provides a solid basis for moving on to future trials, such as the Classical Assumption Test and the Regression Test.